The Effect of Variations in Sulfuric Acid - Oxalic Acid Electrolyte Concentration and Additional Aeration on 1100 Series Aluminum Anodization Results - Leoanggraini, Unung; Irianto, Indra; Aji, Restu; Paramitha, Tifa; Sihombing, Rony (Journal of Green Science and Technology, 2024)
Aluminum is one of the materials used in making various types of goods because it has good properties such as being light, ductile and has good corrosion resistance. One of the disadvantages of aluminum is its low level of hardness. This can be overcome by treating aluminum, one of which is the anodization process. In this research, variations in the type of electrolyte used were sulfuric acid-oxalic acid, the electrolyte concentration was 16% with an interval of 0.5, the temperature used was room temperature with a current density of 3/dm2 and a coating time of 30 minutes. The aim of this research is to determine the acid concentration and the effect of the aeration system on mechanical properties. From the data obtained, it was found that the difference in weight of the best metal with the addition of aeration at a concentration of 13.5+2.5 was 0.0411 gr. This shows that as the concentration of oxalic acid increases it can accelerate the process of aluminum oxide formation, then for electrolyte concentrations of 16+0, 15.5+0.5, 15+1, 14.5+1.5 and 14+2 the difference in mass weight metals increased respectively by 0.0337 gr, 0.0335 gr, 0.0366 gr, 0.0390 and 0.0411 gr. In the anodization process without   additional aeration, the best metal weight difference is found at an electrolyte concentration of 13.5+2.5 of 0.0401 gr. This shows that increasing the concentration of oxalic acid can accelerate the process of aluminum oxide formation. Then at electrolyte concentrations of 16+0, 15.5+0.5, 15+1, 14.5+1.5 and 14+2 the difference in metal mass weight gradually increases by 0.0182 gr, 0.0293 gr, 0.0318 gr, 0.0322 and 0.0362 gr. Keywords: Aluminum, Anodization, Oxide Coating, Electrolyte Solution, Sulfuric Acid, Oxalic acid